Ten Years after the Adoption of IFRS in Chile (GESTIÓN Y TENDENCIAS, 2019)
The adoption of the International Financial Reporting Standards (IFRS) meant, in the world of finance, a move from a purely rule-bound and inefficient economic culture toward an economic culture interconnected with the dynamic reality of global investment. In Chile, preparations for the change from GAAP (Generally Accepted Accounting Principles) to IFRS began as early as 2004, but the date set for the first changes was 2009, when a column was added showing financial statements under IFRS for comparison with the columns under Chilean GAAP. The year IFRS came fully into force in Chile was in the financial statements for 2010.